The diagnostic value and safety of modified needle aspiration biopsy for superficial lymphadenectasis - Hua, Shaopeng; Hu, Xiaofang; Zhao, Xinguo; Mao, Jia (Frontiers in Surgery, 2022)
Objective: To explore the safety and diagnostic value of modified needle aspiration biopsy for superficial enlarged lymph nodes. Methods: A total of 88 patients with unknown diagnosis of superficial lymphadenopathy in our hospital (Wuxi Fifth People's Hospital) from January 2018 to July 2021 were recruited and then divided into two groups using the simple random grouping method. The study group included 48 patients who were punctured via modified needle aspiration biopsy, while the control group included 40 patients who were punctured via core needle biopsy (CNB) and had a better clinical evaluation. A BARD® automatic biopsy gun with a 18 G needle was used to puncture any enlarged lymph nodes, and specimens were obtained for pathological examination. The diagnostic positive rate of the two puncture methods was then compared and the complications involved in the two methods were observed. Result: The positive rate of definite pathological diagnosis was 79.2% (38/48) in the study group and 82.5% (33/40) in the control group. Both groups had similar diagnostic positive rates regarding tuberculosis and metastatic tumours in the lymph nodes (P > 0.05). Only slight bleeding was observed during the operations using the two puncture methods, with the bleeding rate of the study group 20.8% and that of the control group 15.0%, and the difference was not statistically significant (P > 0.05). No other complications were observed across both groups. Among the 48 patients with enlarged lymph nodes in the study group, there was no difference in the positive rate of diagnosis between enlarged lymph nodes larger than 20 mm and those smaller than 20 mm in the pathological, bacterial culture and cytology examinations (P > 0.05). The sensitivity, specificity, positive predictive values and negative prediction values of the improved lymph node lesions were 83.3%, 100%, 100% and 90.9%, respectively. Conclusion: The diagnostic efficacy and safety of modified needle aspiration biopsy in superficial swollen lymph nodes are equivalent to those of CNB, but the former is a more economical, simple and practical method for clinical settings and one that could be popularised in primary hospitals.